PERBANDINGAN KEANEKARAGAMAN JENIS BURUNG DI TELUK MANADO - Stevano G. Ch. Puasa; Johny S. Tasirin; Terry M. Frans (COCOS, 2018)
ABSTRACTManado Bay is an important area for the growth of Manado city, most of the Manado bay area has undergone development with a variety of good destinations for public facilities, service providers and economies as well as residential areas. The developments that have occurred are driving changes in land cover in the Manado Bay coastline. This study aims to compare the diversity of bird species in the built area and areas that are still natural or not yet developed in the Manado Bay coastline. This research was conducted from September to December 2017 using the Point Count. The results of observations were found in 37 species from 21 families, with the Shannon-Wiener index value 3.13 as an indication of the high diversity of bird species in the Bay of Manado. Keywords : Birds, Bird species diversity, Manado Bay